2016
DOI: 10.1186/s12879-016-1441-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Mycobacterium tuberculosis isolates from Hebei, China: genotypes and drug susceptibility phenotypes

Abstract: BackgroundTuberculosis remains a major public health problem in China. The Hebei province is located in the Beijing-Tianjin-Hebei integration region; however little information about the genetic diversity of Mycobacterium tuberculosis was available in this area. This study describes the first attempt to map the molecular epidemiology of MTB strains isolated from Hebei.MethodsSpoligotyping and 15-locus MIRU-VNTR were performed in combination to yield specific genetic profiles of 1017 MTB strains isolated from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 28 publications
(28 reference statements)
3
22
2
Order By: Relevance
“…Those studies considered that Beijing genotype was associated with drug resistance and those strains showed higher drug resistance level 20 , 21 . Meanwhile, other studies also showed no clearly association relationship between drug resistance and strains clade 13 , 22 .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Those studies considered that Beijing genotype was associated with drug resistance and those strains showed higher drug resistance level 20 , 21 . Meanwhile, other studies also showed no clearly association relationship between drug resistance and strains clade 13 , 22 .…”
Section: Discussionmentioning
confidence: 93%
“…Different results obtained from different studies and different regions possibly because of the amount of Beijing genotype sublineages and the percentage of modern or ancient Beijing genotype, which affected the DST results 22 . In 2006 Mokrousov et al .…”
Section: Discussionmentioning
confidence: 99%
“…And they were identified as the causative agents of tuberculosis in the world. For each families of MTB resistance to rifampicin, the prevalence was analyzed for the selected studies as follows: Beijing nineteen studies [14, 15, 16, 17, 18, 19, 20, 21, 22, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31], LAM ten studies [15, 17, 23, 25, 28, 29, 32, 33, 34, 35], T ten studies [3, 15, 16, 17, 23, 27, 28, 32, 34, 35], EAI eight studies [18, 22, 25, 27, 28, 29, 33, 36], Ural four studies [15, 17, 30, 34] Haarlem five studies [15, 23, 25, 28, 34], CAS four studies [15, 29, 30, 35] and MANU two studies [16, 29]. The proportion of rifampicin resistance varies by the type of regions and strains.…”
Section: Resultsmentioning
confidence: 99%
“…Eigteen studies reported rifampicin resistance Beijing family. Of these studies, nine were conducted in Western Pacific Region, reported 1309 (97.68%) resistance Beijing family [2, 16, 20, 21, 22, 28, 29, 30, 31], three studies were conducted in South-East Asia Region, reported 15 (1.11%) resistance Beijing family [15, 19, 25], two studies were conducted in European Region and identified 14 (1.04%) resistance Beijing family [17, 24] and two studies were conducted in Region of American but only two resistance Beijing family [18, 23]. One study which was conducted in African Region [29] and one study conducted in Eastern-Mediterranean Region did not report a rifampicin resistance Beijing family [30].…”
Section: Resultsmentioning
confidence: 99%
“…Genomic DNA was extracted from mycobacterial colonies grown on L-J medium using a Mericon DNA Bacteria kit (Qiagen, USA), as previously described (30). The expected embB fragment (from codons 207 to 445) was amplified using the following primers: forward-embB (5=-ATC GACACCCGGTTCTCC-3=) and reverse-embB (5=-CTGCACACCCAGT GTGAATG-3=).…”
Section: Methodsmentioning
confidence: 99%